Pengaruh Penerapan Metode Pembelajaran Quiz Team Pada Materi Litosfer Terhadap Hasil Belajar Siswa Kelas X SMA Negeri 6 Depok - Paraanisa, Tika; Mataburu, Ilham Badaruddin; Kusumawati, Lia (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research will aim to find out the result of students’ learning process by implementing the ‘quiz team’ learning method on the Endogenic Forces sub-chapter within the Lithosphere material in SMA Negeri 6 Depok. This research will be apart of the Quasi Experiment with the Group Pre-test and Post-test Design. The sample that is going to be used in this research will be taken with the Purposive Sampling technique. The sample that is going to be used in this research will be grade X IPS 1 as the experiment class which will utilize the ‘quiz team’ learning method during classes and grade X IPS 2 as the control class which will utilize the conventional learning method during classes. The data collection will be conducted in the form of a multiple choices test with 20 questions acting as pre-test and post-test. The testing in this research will use the instrumentation, analytic requirement, and data analysis technique. The result of the data testing that is going to be conducted will reveal the existence of an impact on the learning results of students in the experiment class. The experiment class shall experience a significant increase in learning results with the average grade of 72,50 from 55,78. Whereas the control class shall gain an average of 60,31 from 53,12. This conclusion will be supported by how the Sig. score obtained on the T test will not match for 0,000 meaning is denied and is accepted because the Sig. score is < 0,05. Thus, there will be an impact from the implementation of learning results in the X grade of SMA Negeri 6 Depok after using the ‘quiz team’ learning method during geography class.